The stimulatory effects of asbestos on NADPH-dependent lipid peroxidation in rat liver microsomes. - Fontecave, M (1987)
Lipid peroxidation in rat liver microsomes induced by asbestos fibres, crocidolite and chrysotile, is greatly increased in the presence of NADPH, leading to malondialdehyde levels comparable with those induced by CCl4, a very strong inducer of lipid peroxidation. This synergic effect only occurs during the first minutes and could be explained by an increase or a regeneration of the ferrous active sites of asbestos by NADPH, which in turn could rapidly be prevented by the adsorption of microsomal proteins on the surface of the fibres. It is not inhibited by superoxide dismutase, catalase and mannitol, indicating that oxygen radicals are not involved in the reaction. It is also not inhibited by desferrioxamine, indicating that it is not due to a release of free iron ions in solution from the fibres. Lipid peroxidation in NADPH-supplemented microsomes is also greatly increased upon addition of magnetite. This could be linked to the presence of ferrous ions in this solid iron oxide, since the ferric oxides haematite and goethite are completely inactive.